Analisis dan tanggung jawab travel umrah atas kegagalan pemberangkatan jamaah umrah di kota makassar - Ainun Jariyah Amha; Nurjaya Nurjaya; Aan Aswari (Qawanin Jurnal Ilmu Hukum, 2021)
Abstract: The research entitled "Responsibility of the Umrah Travel Bureau for theFailure of the Departure of Umrah Congregants (Global Tour Case Study)"raises two problem formulations, namely How is Legal Protection forConsumers of Umrah Congregations Who Have Failed Umrah Departures inthe Global Tours case and How is the Responsibility of Service Businesses?Umrah for Problems That Harm Consumers in the Implementation of theUmrah Worship. The research data was collected by means of documentstudies, literature and interviews with representatives of PT. Global Tours asbusiness actors and Umrah Congregations as consumers and the institutionsconcerned. The data obtained were then analyzed qualitatively and presenteddescriptively in accordance with the provisions of the Consumer ProtectionLaw combined with a direct approach to the parties concerned. The results ofthis study indicate that the legal protection of consumers of Umrah services isadequate with the establishment of regulations that can protect Umrahpilgrims as consumers, namely Law Number 8 of 1999 concerning ConsumerProtection, Law Number 13 of 2008 concerning the Implementation of Hajj,Ministerial Regulation Number 8 of 2018 concerning the Organization ofUmrah Worship Trips, and Law Number 10 of 2009 concerning Tourism, onlythat the legal protection for Umrah pilgrims as consumers has not been fulfilledoptimally in its implementation.The responsibility of business actors is chargedwith criminal responsibility in Article 372 of the Criminal Code regardingembezzlement, Article 378 of the Criminal Code on fraud, and Article 2paragraph (1) of Law Number 8 of 2010 concerning the Prevention andEradication of the Crime of Money Laundering, and administrative liability byrevoking the company's license. PT. Global Tours. Based on the results of thisstudy, the authors suggest that Umrah pilgrims must be careful in choosing aTravel Bureau and pilgrims should find out the legality of the selected UmrahTravel Bureau, to avoid losses for Umrah pilgrims as consumers. Abstrak: Penelitian yang berjudul “Tanggung Jawab Biro Travel Umrah Atas KegagalanPemberangkatan Jemaah Umrh (Studi Kasus Global Tour)” ini mengangkat duarumusan masalah, yakni Bagaimana Perlindungan Hukum bagi KonsumenJemaah Umrah yang Mengalami Kegagalan Keberangkatan Umroh kasusGlobal Tours serta Bagaimana Tanggung Jawab Pelaku Usaha Jasa Umroh atasPermasalahan yang Merugikan Konsumen dalam Pelaksanaan Ibadah Umrah.Data penelitian ini dikumpulkan dengan cara studi dokumen, pustaka danwawancara kepada perwakilan PT. Global Tours selaku pelaku usaha sertaJemaah Umrah selaku konsumen dan Lembaga yang bersangkutan. Data yangdiperoleh kemudian dianalisis secara kualitatif dan dipaparkan secara deskriptif sesuai dengan ketentuan-ketentuan Hukum Perlindungan Konsumendipadukan pendekatan secara langsung kepada para pihak yangbersangkutan. Hasil studi ini menunjukkan bahwa perlindungan hukumkonsumen jasa umroh sudah memadai dengan dibentuknya peraturan yangdapat melindungi para jemaah umrah selaku konsumen yakni Undang-undangNomor 8 Tahun 1999 tentang Perlindungan Konsumen, Undang-undangNomor 13 Tahun 2008 tentang Penyelenggaraan Ibadah Haji, PeraturanMenteri Nomor 8 Tahun 2018 tentang Penyelenggaraan Perjalanan IbadahUmrah, dan Undang-undang Nomor 10 Tahun 2009 tentang Kepariwisataan,hanya saja dalam perlindungan hukum bagi para jemaah umrah selakukonsumen belum terpenuhi secara maksimal dalam pelaksanaanya.Pertanggungjawaban pelaku usaha dibebankan pada pertanggungjawabanpidana Pasal 372 KUHP tentang penggelapan, Pasal 378 KUHP tentangpenipuan, dan Pasal 2 ayat (1) Undang-undang Nomor 8 Tahun 2010 tentangPencegahan dan Pemberantasan Tindak Pidana Pencucian Uang, danpertanggungjawaban administratif yakni dengan mencabut izin perusahaanPT. Global Tours. Berdasarkan hasil penelitian ini penulis menyarankan bahwapara jemaah umrah harus berhati-hati dalam memilih Biro Travel danhendaknya para jemaah mencari tau legalitas dari Biro Perjalanan Umrahyang telah dipilih, untuk menghindari timbulnya kerugian bagi para jemaahumrah selaku konsumen